The current state of forensic imaging – recommended radiological tools and international guidelines - Fabrice, Dedouit; Mathilde, Ducloyer; Jamie, Elifritz; Natalie, L. Adolphi; Yi-Li Grace, Wong; Summer, Decker; Jonathan, Ford; Yanko, Kolev; Michael, Thali (SPRINGER, 2025)
The last few decades have seen the emergence of forensic imaging, both clinical and post-mortem. Year after year, the scienti c community has re ned the radiological tools that can be used for post-mortem and clinical forensic purposes. As a result, scienti c societies have published recommendations that are essential for the daily work of forensic imaging. This third part of the review of the current state of forensic imaging describes these recommended radiological tools and also presents an overview of the various international guidelines dealing with post mortem imaging that can be found in the literature or that have been written by scienti c societies.